Analysis of the Relationship between the Standard Precipitation Index in South Vietnam and Sea Surface Temperature - Van Viet, Luong (VNU Journal of Science: Earth and Environmental Sciences, 2022)
This study investigated the correlation coefficient between sea surface temperature (SST) and the standard precipitation Index (SPI) at stations in south of Vietnam. The data included in this survey are the precipitation of 47 stations in South Vietnam and the field of SST from the NCEP/NCAR Reanalysis for the period between 1979 and 2019. The results show that with a single region, SST in the Niño 3.4 region has the best relationship with SPI in the study area. Using multiple correlation analysis, this study found a region between 115 o E and 130 o E and latitude from 15 o S to 25 o N, combined with the Niño 3.4 region SST they create a pair that has the best relationship with SPI in the study area. Based on an assessment of the critical value of the Pearson correlation coefficient corresponding to the significance level of 99%, this pair had a good relationship with SPI between October and May of the following year. By conducting a partial correlation analysis when removing the role of Niño 3.4 also showed that SST in the Bien Dong also plays an important role in the fluctuation of SPI in South Vietnam.